2013
DOI: 10.1088/0953-8984/25/15/155701
|View full text |Cite
|
Sign up to set email alerts
|

Observation of superconductivity in the intermetallic compound β-IrSn4

Abstract: Low-temperature dc-magnetization, ac electrical resistivity and specific heat measurements were performed on single crystals of the intermetallic compound β-IrSn4. The compound crystallizes in the tetragonal MoSn4-type structure (space group I41/acd) and exhibits superconductivity below Tc = 0.9 ± 0.05 K. Further, the magnitude of the ratios ΔCp/(γnkBTc) = 1.29, 2Δ/(kBTc) = 3.55 and of the electron-phonon coupling λ[overline](e-ph) = 0.5 imply that superconductivity in β-IrSn4 can be ascribed to a s-wave weak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
(43 reference statements)
2
10
0
Order By: Relevance
“…Based on this, two different assumptions can be made: either (i) KBi 2 is a type-II SC that the upper critical field H c2 is very small and close to the lower critical field H c1 ; or (ii) KBi 2 is a type-I SC and the departure from the ideal step-like transition at critical field may be attributed to a strong pinning of domain walls in the intermediate state or to unclear demagnetization. 23 For the latter case, the critical field H c is defined as the field where the sample enters to the normal state (M (H) = 0). On the other hand, when temperature decreases, the critical field shifts to higher field.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, two different assumptions can be made: either (i) KBi 2 is a type-II SC that the upper critical field H c2 is very small and close to the lower critical field H c1 ; or (ii) KBi 2 is a type-I SC and the departure from the ideal step-like transition at critical field may be attributed to a strong pinning of domain walls in the intermediate state or to unclear demagnetization. 23 For the latter case, the critical field H c is defined as the field where the sample enters to the normal state (M (H) = 0). On the other hand, when temperature decreases, the critical field shifts to higher field.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 shows isothermal magnetization loop M (H) at T = 2 K. The shape of the curve is nearly typical for type-I superconductor, however it reveals a small hysteresis. Such hysteresis is observed in other compounds considered to be type-I superconductors and, generally, is associated with sample shape effects, domain or grain walls etc [29,[31][32][33][34]. Temperature dependences of the specific heat in various magnetic fields are shown on Fig.…”
Section: Resistivity Specific Heat and Magnetic Susceptibilitymentioning
confidence: 87%
“…This effect is observed for mixed state of type-I superconductors or in type-II superconductors with close H c1 and H c2 values. considered to be type-I superconductors and, generally, is associated with sample shape effects, domain or grain walls etc [29,[31][32][33][34]. Temperature dependences of the specific heat in various magnetic fields are shown on Fig.…”
Section: Resistivity Specific Heat and Magnetic Susceptibilitymentioning
confidence: 99%
“…It was surprising enough that superconductivity in the β-IrSn 4 phase was observed by Tran et al 7 Based on experimental data, the authors suggested that the presence of superconductivity in β-IrSn 4 is due to a weak electron–phonon pairing, even if the possible existence of d-electrons favors strong correlation. 7 The discovery of superconductivity in β-IrSn 4 invites further investigation, not only due to the fact that strong correlations are often the origin of many interesting physical phenomena in materials, such as metal–insulator transitions, magnetic ordering, and superconductivity, 8,9 but also owing to the need to answer some crucial questions, e.g. : (i) how does the strong electron correlation affect the superconductivity of β-IrSn 4 ?…”
Section: Introductionmentioning
confidence: 99%